Impactful communication : communicate to conquer - Sethi, Deepa (Thousand Oaks : SAGE Publications Inc, 2021)
"In today's fast-paced world of artificial intelligence and social media, Impactful Communication is your mantra to success. The book empowers you with tools to effectively deal with the conventional and nonconventional aspects of verbal and nonverbal communication in varied situations"--